Shot peening of austempered ductile iron gears. (2nd September 2017) - Zammit, Ann; Bonnici, Matthew; Mhaede, Mansour; Wan, Rui; Wagner, Lothar
ABSTRACT: This study investigates the suitability of shot peening as a surface treatment for austempered ductile iron (ADI) gears to lengthen their service life. Several studies have shown that shot peening prolongs the bending fatigue life of components. However, from the few works conducted on the tribological behaviour of ADI, it is not clear whether an improvement exists by shot peening. Hence, this work was conducted to study the contact fatigue resistance of shot peened ADI gears. Tests on as-ADI and shot peened ADI gears, as well as carburised steel gears were carried out. The results showed that the carburised steel gears exhibited superior performance and withstood the longest number of cycles before failure. The shot peened gears survived the lowest number of cycles. The poor performance after shot peening was attributed to an increase in the surface roughness induced by the peening process. In fact, the negative impact resulting from the roughened surface is greater than the benefits prompted by the induced compressive residual stresses, higher surface hardness and stress-induced austenite to martensite transformation.